2019
DOI: 10.1111/1468-0009.12437
|View full text |Cite
|
Sign up to set email alerts
|

Is Moderate Drinking Protective Against Heart Disease? The Science, Politics and History of a Public Health Conundrum

Abstract: For more than 40 years, most research by epidemiologists, social scientists, and alcohol policy experts found that moderate alcohol consumption was cardioprotective. In the early 2000s, that consensus was shaken by new critics who subjected the previous research to vigorous methodological and empirical analysis, precipitating a bitter controversy, seemingly unresolvable despite numerous observational epidemiological studies. The effort to finally put that debate to rest through a large, multiyear randomized co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…There are conflicting studies about the effects of drinking on CVD/MI. Some studies have shown an effect of drinking on CVD/MI [25], while others have found no such association [26]. This study's findings support no relationship between drinking and CVD/MI.…”
Section: Behavioral Factorssupporting
confidence: 55%
“…There are conflicting studies about the effects of drinking on CVD/MI. Some studies have shown an effect of drinking on CVD/MI [25], while others have found no such association [26]. This study's findings support no relationship between drinking and CVD/MI.…”
Section: Behavioral Factorssupporting
confidence: 55%
“…There are conflicting studies about the effects of drinking on CVD/MI. Some studies have shown an effect on drinking on CVD/MI [26], while others have found no such association [27]. This study's findings support no relationship between drinking and CVD/MI.…”
Section: Discussionsupporting
confidence: 55%
“…After millennia of use, it is disturbing indeed that no such randomized trial has been conducted. The major obstacle to such a trial appears to be an asymmetric fear of what it might show, restricted to those who favour complete abstention and/or prohibition [46]. Without a trial, the evidence base on which to judge a safe level of alcohol consumption is relegated to be substandard and inconclusive and, worst of all, intentionally engineered that way.…”
Section: Generating New Evidence To Support Guideline Developmentmentioning
confidence: 99%